Thermostructural shape memory effect observations of ductile Cu-Al-Mn smart alloy - Canbay, Canan Aksu; Karaduman, Oktay; Ibrahim, Pshdar A.; Ozkul, Iskender (Techno-Press, 2021)
The Cu-Al-Mn shape memory alloy (SMA) with a new different composition was fabricated by arc melting method. The characteristic shape memory effect (SME) property of Cu-Al based SMA was revealed by performing thermostructural measurements. The differential scanning calorimetry (DSC) tests were taken to observe the reversible martensitic phase transformation peaks of the alloy as evidence of SME property of the alloy. To determine the basic thermodynamical parameters of the alloy, these endothermic and exothermic transformation peaks were analyzed by the tangent differentiation method that was performed automatically by the DSC analyzing program over a manually selected part on the DSC curve and by these analyses the characteristic martensitic transformation temperatures (working temperatures) that found below 100 degrees C and the enthalpy change values of the alloy were directly obtained. The other kinetic transformation parameters of the alloy - the entropy change, hysteresis, and equilibrium temperature - were also determined. The common high-temperature behavior of the Cu-Al based Heusler alloys was detected by differential thermal analysis (DTA) measurement. The XRD and metallography tests that were conducted at room temperature showed the presence of M18R and the dominant 2H martensite structures that formed in the alloy and this dual martensitic structure was also prescribed by determining the theoretical e/a ratio of the alloy. Furthermore, the microhardness tests on the alloy demonstrated the high ductility feature of the alloy. All results demonstrated that the CuAlMn alloy exhibiting a shape memory effect property can be useful in smart alloy applications.
Keywords: shape memory alloy; CuAlMn Heusler alloy; ductility; entropy; shape memory effect; martensite; DSC; DTA; XRD; optical metallography